Conditions : ten : a feminist magazine of writing by women with an emphasis on writing by lesbians - Derricotte, Toi; Umpierre, Luzma; Peri Rossi, Christina (Baltimore : Conditions, 1984)
Fonds Suzan Daniel (FSD)
Engels
Monografie